Vespa Motorcycle Marketing by Using Augmented Reality Markerless Method Based on Android - Butsiarah; Muh. Ilham Ramadhan; Kamaruddin; Supriadi Sahibu (Yayasan Cendekiawan Digital Indonesia (CEDDI), 2022)
The problem that occurred was CV. Scootres Group had not had a marketing application so it was difficult to serve the buyers who wanted to buy a Vespa when they were far from the location. Sometimes the seller has to answer the questions one by one from the buyers. This study aims at creating an Android-Based Vespa Motorcycle Marketing application to facilitate marketing on the CV. Scoots Group. The data was obtained through Field Research, Library Research, and interview. Then the system design stage, application creation, and testing stage. The SDK used is EasyAR and the C programming language and the method used in this research is the Markerless method. The results of the study indicate that the system used is BlackBox testing and User Acceptance Test (UAT) based on BlackBox testing, the system is running well, and based on UAT testing 10 respondents with a percentage of 85% and 2 Expert Examiners with a percentage of 89%, both are included in the category strongly agree to apply.